Analisis Faktor-Faktor Yang Mempengaruhi Minat Kunjungan Wisata Pantai Padang, Sumatera Barat - Novesar, Muhammad Refki (Politeknik Pariwisata Medan, 2023)
Padang Beach is a beach located in Padang City, West Sumatra. This beach is situated in a densely populated urban area in the West Padang District. The author aimed to determine the factors and their respective impacts, particularly the most significant factor, on tourist interest. In this research, 150 respondents who had visited Padang Beach more than twice were surveyed. The sampling method used in this study was purposive sampling, encompassing five variables: Tourism Product Quality, Tourism Product Image, Customer Value, Product Attractiveness, and Repeat Visit Intention. Hypothesis testing was carried out using regression analysis, and the results concluded that these factors significantly influence the tourist interest and the number of visitors to Padang Beach. The research findings indicate that tourists are attracted to visit Padang Beach for a second time or even more, taking into account the quality, image, customer value, and attractiveness of the beach itself. The beach's unique qualities undoubtedly play a vital role in attracting tourists to Padang Beach. Keyword : Tourism Product Quality, Tourism Product Image, Customer Value, Product Attractiveness, and Repeat Visit Intention.